Analisis Pelatihan Pemanfaatan E-Commerce Dalam Meningkatkan Jangkauan Pemasaran Produk UMKM - Qurrota'ayun, Latifatul Ummi (Amsir Management Journal, 2024)
The development of the globalization era has created an increasingly rapid digital era. This situation demands the adaptation of various parties to the new environment, including economic actors, and small, medium and large businesses. One of the new lifestyles that was born is shopping via the internet or often referred to as e-commerce. The use of e-commerce is not only carried out by large companies but also by micro, small and medium enterprises (UMKM). This research was conducted to analyze the use of e-commerce in order to increase the marketing reach of UMKM products for woven craftsmen in Babatan, Ponorogo Regency. The research method used in this study is a qualitative method with a case study approach. The results of the study show that the use of e-commerce will be able to provide income, train MSME actors to become more planned, managed and controlled entrepreneurs, make the products sold quality and more easily recognized by consumers. In addition, the use of e-commerce can also save on promotion costs. This will ultimately be able to increase the reach of product marketing for MSME players in Babatan, Ponorogo Regency.